2014
DOI: 10.3109/13561820.2014.921899
|View full text |Cite
|
Sign up to set email alerts
|

The development of clinical reasoning and interprofessional behaviors: service-learning at a student-run free clinic

Abstract: This article examines the benefits of a student run free clinic (SRFC) as a service learning experience for students in medicine, pharmacy, occupational therapy, physical therapy and physician assistant programs. We hypothesized that students who participate in an interprofessional service learning course and volunteer at a SRFC would demonstrate significant increases in perceptions and attitudes for working in interprofessional health care teams and clinical reasoning skills compared to students who did not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
97
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(137 citation statements)
references
References 30 publications
11
97
0
2
Order By: Relevance
“…Experiential learning has been found to enhance confidence levels of occupational therapy students (Giles et al, 2014;Knecht-Sabres, 2010;Seif et al, 2014). Students showed more competent clinical skills such as assessment and intervention planning, therapeutic use of self and awareness of client resources when provided with an opportunity to deliver occupational therapy services to clients in the community with guided supervision, as determined by Knecht-Sabres (2010).…”
Section: Experiential Learning As a Teaching Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiential learning has been found to enhance confidence levels of occupational therapy students (Giles et al, 2014;Knecht-Sabres, 2010;Seif et al, 2014). Students showed more competent clinical skills such as assessment and intervention planning, therapeutic use of self and awareness of client resources when provided with an opportunity to deliver occupational therapy services to clients in the community with guided supervision, as determined by Knecht-Sabres (2010).…”
Section: Experiential Learning As a Teaching Methodsmentioning
confidence: 99%
“…Other reasons some students failed their Level II fieldwork was due to difficulty accepting feedback and seeing the global impact of their actions. Seif et al (2014) reported that hands-on experience with clients was necessary to develop entry-level clinical reasoning skills.…”
Section: Fieldwork Readinessmentioning
confidence: 99%
“…25 We observed that a high percentage of medical and pharmacy students agreed that working with students from another profession enhances student education and future abilities to work on an interprofessional team, and that all health profession students should be educated to establish collaborative relationships with members from other professions, which is similar to the findings of many other studies. 7,[18][19][20]23 The majority of students agreed that physicians and pharmacists should collaborate in teams and that medical and pharmacy students should be involved in teamwork during their education in order to understand their respective roles. These perceptions were measured towards the end of the spring semester, just before the standardized objective behavioral assessment.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11]17,20,23 Shrader and colleagues demonstrated that student perceptions, collected with an attitudinal survey instrument, were not a significant predictor of clinical outcome scores, whereas teamwork scores, rated by trained observers using a checklist, were a significant predictor of clinical outcome scores. 11 Our standardized objective behavior assessment followed a similar model and involved trained observers evaluating student team behaviors using a checklist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation